2016
DOI: 10.1016/s2095-3119(15)61312-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dwarf mutants and molecular mapping of a dwarf locus in soybean

Abstract: Plant height is one of the most important traits in soybean. The semi-dwarf soybean cultivars could improve the ability of lodging resistance to obtain higher yield. To broaden the dwarfism germplasm resources in soybean, 44 dwarf mutants were identified from a gamma rays mutagenized M 2 population. Two of these mutants, Gmdwf1 (Glycine max dwarf 1) and Gmdwf2 (Glycine max dwarf 2), were investigated in this study. Genetic analysis showed that both mutants were inherited in a recessive manner and their mutated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…Hedou 12 and Williams 82 were obtained from the Chinese Academy of Agricultural Sciences, and the Gmilpa1 mutant was created in our laboratory (Cheng et al, 2016). Wild-type Arabidopsis (Arabidopsis thaliana) and the apc8 mutant (Zheng et al, 2011) were obtained from Dr. Binglian Zheng at Fudan University.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Hedou 12 and Williams 82 were obtained from the Chinese Academy of Agricultural Sciences, and the Gmilpa1 mutant was created in our laboratory (Cheng et al, 2016). Wild-type Arabidopsis (Arabidopsis thaliana) and the apc8 mutant (Zheng et al, 2011) were obtained from Dr. Binglian Zheng at Fudan University.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Plant height is generally controlled by node number on the main stem and internode length. We also found that the significantly decreased cell length contributed to the shortened internode, resulting in the sharp decrease in plant height of dw compared to wild type, while other dwarf soybean mutants mainly exhibited a substantial change in node number, internode length, or both (Hwang et al 2015 ; Cheng et al 2016 ). Furthermore, we mapped the GmDW1 gene to a 460-kb region on Chr.…”
Section: Discussionmentioning
confidence: 68%
“…The dw mutant is quite different from a few other soybean dwarf mutants that have been intensively studied recently. Of them, the Gmdwarf1 mutant slightly responded to GA 3 treatment (Zhang et al 2014 ), while dwarfism of Gmdwf1 could not be rescued by GA 3 application (Cheng et al 2016 ). The FN dwarf mutant, screened from an FN-mutagenized M4 population of Williams 82, began to display abnormal plant height after the V2 stage (Hwang et al 2015 ), however, the dw mutant in our study showed a consistent dwarf phenotype from the cotyledon expansion stage to maturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty progeny of each M 2 line were sowed in the field for phenotyping during May to October 2014. The screened mutant plants were backcrossed for four generations to purify the genetic background from July 2014 to October 2016 in both greenhouse and filed as described before (Chen et al, 2016). One of pale green leaf mutant, named as Glycine max pale green leaf 1 ( Gmpgl1 ), was selected to mapping the mutation locus and function study.…”
Section: Methodsmentioning
confidence: 99%